Preparation method of composite coating of titanium alloy cutting tool
Through composite coating technology, the problems of high temperature, easy adhesion and easy breaking of titanium alloy cutting processing are solved, which significantly improves the cutting life and high temperature resistance of titanium alloy cutting tools, and solves the problem that existing coatings cannot meet severe processing Problems with working conditions.
Patent Information
- Application Number
- CN202411101111.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-31
AI Technical Summary
The high strength and low thermal conductivity of titanium alloys lead to low cutting efficiency and poor surface quality. The tool is often easily broken due to adhesive wear and short cutting life. The existing single coating cannot meet the severe processing conditions.
Using the composite coating preparation method, the gradient biased TiAlN coating, nano TiAlN/VN alternating coating and VN coating are deposited through vacuum plasma plating equipment, combined with cathode arc ion plating and magnetron sputtering technology to form high temperature friction reduction, Antioxidant and low stress coating.
Significantly improve the cutting life of titanium alloy cutting tools, enhance high temperature resistance and mechanical properties, reduce the surface roughness and residual stress of the coating, and enhance the comprehensive performance of the tool.
Smart Images

Figure CN119220938A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloy cutting tools, and in particular relates to a method for preparing a composite coating of a titanium alloy cutting tool. Background Art
[0002] Titanium alloy has the characteristics of low density, high wear resistance and high strength, making it widely used in the manufacture of major structural parts such as aircraft landing gear, wing shaft beams and actuators. However, due to the high strength, high toughness and low thermal conductivity of titanium alloy, its machinability is very poor. During the cutting process, it often causes severe adhesive wear and even tool breakage due to sticking of the tool, which greatly reduces the tool life. The low cutting efficiency, poor surface quality and easy chipping of titanium alloy have always been key technical problems that materials and mechanical workers have been working hard to solve.
[0003] With the development of tool technology, tool coating is an important way to improve the cutting life of tools. However, a single type of coating can no longer meet the increasingly severe processing conditions. Coating diversification and nano-ization have become the trend in the coating field. Therefore, it is urgent to design a new composite coating preparation method to improve the cutting life of titanium alloy processing tools. Summary of the invention
[0004] In order to solve the problems of high temperature, easy adhesion and easy tool breakage occurring during the cutting process of titanium alloy machining tools, the present invention provides a method for preparing a composite coating for titanium alloy cutting tools. The composite coating prepared by this method has the advantages of high-temperature friction reduction, anti-oxidation and low stress, and can significantly improve the cutting life of titanium alloy machining tools.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for preparing a composite coating of a titanium alloy cutting tool, the preparation method comprising:
[0007] S1. Place the clean surface substrate material into the furnace chamber of the vacuum plasma plating equipment and evacuate the chamber;
[0008] S2. Use Ar + 、Ti + and Al + Etching the base material;
[0009] S3. Depositing a TiAlN coating on the surface of the substrate material using a gradient bias process;
[0010] S4. Depositing a nano-TiAlN / VN alternating coating on the surface of the TiAlN coating;
[0011] S5. A VN coating is deposited on the surface of the nano-TiAlN / VN alternating coating by a gradient bias process;
[0012] S6. Using Ar + The surface of the VN coating is polished.
[0013] Furthermore, the step of placing the substrate material with a clean surface into a furnace chamber of a vacuum plasma plating device and evacuating the chamber specifically includes:
[0014] The surface of the substrate material was ground and polished, then ultrasonically cleaned in ethanol, dried, and placed in the furnace of a vacuum plasma plating device to evacuate the surface to a vacuum degree of 3 to 6 × 10 -3 Pa.
[0015] Further, the use of Ar + 、Ti + and Al + Etching the base material includes:
[0016] Heat the base material to 400°C, set the base material bias voltage to -120 to -150V, and introduce 150 to 350
[0017] sccm of argon to Ar on the surface of the substrate + Etching, etching time 10 to 30 minutes;
[0018] The base material is set to a bias voltage of -800 to -1000 V, the cathode arc TiAl target is turned on, the distance between the TiAl target and the base material is 5 cm, the target current is 60 to 200 A, the rated power is 20 kW, and the duty cycle is 45% to perform high-energy ion Ti on the base material. + and Al + Etching, etching time 5 to 15 minutes.
[0019] Furthermore, the step of depositing a TiAlN coating on the surface of the substrate material using a gradient bias process specifically includes:
[0020] Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total flow of the two gases is 300-500sccm, the working targets are 3 cathode arc TiAl targets, the target current is 60-200A, the frequency is 30-70KHz, the duty cycle is 30%-80%, the bias gradient of the substrate material increases in steps of 20V, the bias changes are 0V, -20V, -40V and -80V respectively, and the deposition time is 20-40min to achieve the deposition of TiAlN coating on the surface of the substrate material.
[0021] Furthermore, the step of depositing a nano-TiAlN / VN alternating coating on the surface of the TiAlN coating specifically includes:
[0022] Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total gas flow is 300-500sccm, the rotation speed of the substrate material is 2-6rpm, the working targets are three cathode arc TiAl targets and one magnetron sputtering V target, the target current is 5-200A, the frequency is 30-70KHz, the duty cycle is 30%-80%, the substrate material bias voltage is -80V, the deposition time is 10-20min, and the deposition of nano TiAlN / VN alternating coating on the surface of the TiAlN coating is achieved, and the modulation ratio is 1:4.
[0023] Furthermore, the step of depositing a VN coating on the surface of the nano-TiAlN / VN alternating coating by using a gradient bias process specifically includes:
[0024] Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total gas flow rate is 300-500sccm, the working target material is a magnetron sputtering V target, the target current is 5-20A, the frequency is 30-70KHz, the duty cycle is 30%-80%, the matrix material bias growth step is 20V, the bias changes are 0V, -20V, -40V and -80V respectively, and the deposition time is 10-30min, so as to realize the deposition of VN coating on the surface of the nano TiAlN / VN alternating coating.
[0025] Furthermore, the use of Ar + Polishing the surface of the VN coating specifically includes:
[0026] 150-350 sccm of argon gas is introduced into the furnace chamber, the substrate material is biased at -100--200 V, and the polishing time is 5-30 min, until the surface roughness of the VN coating reaches Ra=5-15 nm.
[0027] Furthermore, in terms of atomic percentage, in the cathode arc TiAl target, the content of Ti is 10-30%, and the content of Al is 70-90%.
[0028] Furthermore, the matrix material includes any one of cemented carbide, metal ceramic, stainless steel, single crystal silicon wafer, ceramic silicon plate and titanium alloy.
[0029] Based on the same inventive concept, the present invention provides a titanium alloy cutting tool, which is prepared by the above-mentioned composite coating preparation method for a titanium alloy cutting tool.
[0030] Further, the tool comprises a tool base material, a TiAlN coating, a nano-TiAlN / VN alternating coating and a VN coating are sequentially deposited on the surface of the tool base material, the TiAlN coating has a thickness of 0.8 to 1.5 μm, the total thickness of the nano-TiAlN / VN alternating coating is 0.1 to 0.5 μm, the modulation ratio is 1:4, and the VN coating has a thickness of 0.5 to 1 μm;
[0031] In the VN coating and the VN layer in the nano-TiAlN / VN alternating coating, the atomic percentage of V is 45 to 69 at.%, and the atomic percentage of N is 31 to 55 at.%;
[0032] In the TiAlN coating and the TiAlN layer in the nano-TiAlN / VN alternating coating, the atomic percentage of each element is as follows:
[0033] Ti: 11% to 29%, Al: 22% to 33%, N: 41% to 73%.
[0034] Based on the same inventive concept, the present invention provides a use of a titanium alloy cutting tool in cutting materials with high strength and low thermal conductivity, wherein the material with high strength and low thermal conductivity includes any one of titanium alloy, ultra-high strength steel and high-temperature alloy.
[0035] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0036] 1. The present invention discloses a method for preparing a composite coating for a titanium alloy cutting tool. The TiAlN coating and the VN coating are deposited by a gradient bias method. The deposited coatings have low stress, high bonding strength and thermal crack propagation resistance. When working at high temperature, the TiAlN in the composite coating produces Al2O3 to prevent the coating from further oxidation. The V2O5 produced by the VN coating has a low high-temperature friction coefficient, which significantly improves the high-temperature resistance of the titanium alloy cutting tool. The nano-TiAlN / VN alternating coating in the composite coating has a special modulation ratio of 1:4, which ensures the coherent growth of the coating. At the same time, the boundary dislocation pinning effect produced between the coating interfaces promotes interface strengthening. Therefore, the composite coating prepared by the present invention has excellent comprehensive performance and can effectively improve the cutting life of the titanium alloy cutting tool.
[0037] 2. A composite coating preparation method for a titanium alloy cutting tool of the present invention, wherein the method adopts cathode arc ion plating to prepare an inner layer TiAlN coating in the composite coating, a negative bias voltage with a gradient change is set on the substrate material to increase the deposition rate gradient of TiAlN, and the energy of the ions is gradually increased, and the obtained gradient continuous structure is conducive to stress relaxation of the coating, cathode arc ion plating and magnetron sputtering are used to simultaneously prepare a nano TiAlN / VN alternating coating, wherein the modulation ratio of the TiAlN and VN coatings is 1:4, and this modulation ratio meets the coherent growth condition, the surface VN coating in the composite coating is prepared by magnetron sputtering, and a negative bias voltage with a gradient change is set on the substrate, and finally the coating surface is polished by argon plasma, and after Ar + Bombardment, the coating surface is nano-polished, the number of droplets is reduced, which is beneficial to reduce the surface roughness of the coating and reduce the residual stress of the coating.
[0038] 3. The present invention discloses a titanium alloy cutting tool, the surface of which has a composite coating, which includes, from the inside to the outside, a gradient bias TiAlN coating, a boundary dislocation strengthened nano TiAlN / VN alternating coating and a gradient bias VN coating, wherein the gradient bias TiAlN coating has a thickness of 0.8 to 1.5 μm, the total thickness of the nano TiAlN / VN alternating coating is 0.1 to 0.5 μm, and the modulation ratio is 1:4, which satisfies the conditions for coherent growth due to the template effect, and at the same time, boundary dislocations are formed at the interface between the nano alternating layers, and dislocation pinning promotes the interface strengthening effect, and the gradient bias VN coating has a thickness of 0.5 to 1 μm. The composite coating of the tool of the present invention has the characteristics of strong high-temperature friction reduction on the surface, oxidation resistance, excellent internal mechanical properties, small residual stress between coatings and high bonding strength, thereby significantly improving the cutting life of the titanium alloy processing tool. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0040] Figure 1 This is the cross-sectional electron scanning microscopic morphology of the TiAlN-nano TiAlN / VN-VN composite coating prepared in Example 1 of the present invention.
[0041] Figure 2 This is the scratch morphology of the TiAlN-nano TiAlN / VN-VN composite coating prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0042] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0043] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0044] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0045] The technical principle of the present invention is as follows:
[0046] The present invention provides a method for preparing a composite coating of a titanium alloy cutting tool, the preparation method comprising:
[0047] S1. Place the clean surface substrate material into the furnace chamber of the vacuum plasma plating equipment and evacuate the chamber;
[0048] S2. Use Ar + 、Ti + and Al + Etching the base material;
[0049] S3. Depositing a TiAlN coating on the surface of the substrate material using a gradient bias process;
[0050] S4. Depositing a nano-TiAlN / VN alternating coating on the surface of the TiAlN coating;
[0051] S5. A VN coating is deposited on the surface of the nano-TiAlN / VN alternating coating by a gradient bias process;
[0052] S6. Using Ar + The surface of the VN coating is polished.
[0053] Step S1 specifically includes:
[0054] The surface of the substrate material was ground and polished, then ultrasonically cleaned in ethanol, dried, and placed in the furnace of a vacuum plasma plating device to evacuate the surface to a vacuum degree of 3 to 6 × 10 -3 Pa.
[0055] Step S2 specifically includes:
[0056] Heat the base material to 400°C, set the base material bias voltage to -120 to -150V, and introduce 150 to 350
[0057] sccm of argon to Ar on the surface of the substrate + Etching, etching time 10 to 30 minutes;
[0058] The substrate material was set to a bias voltage of -800 to -1000 V, and three cathode arc TiAl targets were turned on. The distance between the TiAl target and the substrate material was 5 cm, the target current was 60 to 200 A, the rated power was 20 kW, and the duty cycle was 45% to perform high-energy ion Ti on the substrate material. + and Al + Etching, etching time 5 to 15 minutes.
[0059] In the present invention, the surface of the substrate is subjected to Ar + The purpose of etching is to clean the surface contamination of the substrate and to perform high-energy ion Ti on the surface of the substrate material. + and Al + The purpose of etching is to create nucleation growth points on the surface to facilitate the nucleation and growth of grains.
[0060] Step S3 specifically includes:
[0061] Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total flow rate of the mixed gas is 300-500sccm, the working targets are 3 cathode arc TiAl targets, the target current is 60-200A, the frequency is 30-70KHz, the duty cycle is 30%-80%, the step size of the bias gradient increase of the substrate material is 20V, the bias changes are 0V, -20V, -40V and -80V respectively, and the deposition time is 20-40min to achieve the deposition of TiAlN coating on the surface of the substrate material.
[0062] In the present invention, the purpose of introducing argon and nitrogen into the furnace chamber is to form Ar + Bombard the substrate surface to remove impurities. At the same time, Ar + Bombarding the target makes Al + and Ti + Adsorbed on the substrate.
[0063] In the present invention, the advantage of depositing a TiAlN coating on the surface of the substrate material is that the coating has a high surface hardness and is more wear-resistant, which plays a certain protective role on the substrate. Secondly, at high temperatures, TiAlN will combine with oxygen to generate TiO2 and Al2O3, which effectively reduces the surface friction coefficient.
[0064] In the present invention, the TiAlN and VN coatings in the composite coating are obtained by gradient bias deposition, and the ion energy gradient changes and is deposited on the substrate. The obtained coating structure has a continuous transition, and the coating has low residual stress and strong bonding force.
[0065] Step S4 specifically includes:
[0066] Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total flow of the mixed gas is 300-500sccm, the rotation speed of the substrate material is 2-6rpm, the working target materials are three cathode arc TiAl targets and one magnetron sputtering V target, the target current is 5-200A, the frequency is 30-70KHz, the duty cycle is 30%-80%, the substrate material bias voltage is -80V, the deposition time is 10-20min, and the deposition of nano TiAlN / VN alternating coating on the surface of the TiAlN coating is achieved, and the modulation ratio is 1:4.
[0067] Step S5 specifically includes:
[0068] Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total flow of the mixed gas is 300-500sccm, the working target material is a magnetron sputtering V target, the target current is 5-20A, the frequency is 30-70KHz, the duty cycle is 30%-80%, the matrix material bias growth step is 20V, the bias changes are 0V, -20V, -40V and -80V respectively, and the deposition time is 10-30min, so as to realize the deposition of VN coating on the surface of the nano TiAlN / VN alternating coating.
[0069] In the present invention, the advantage of using VN coating as the surface layer of the composite coating is that VN is a transition layer, which is closely combined with the substrate and the TiAlN coating, and has a certain energy absorption effect, which can prevent the cracks caused by impact from spreading.
[0070] Step S6 specifically includes:
[0071] 150-350 sccm of argon gas is introduced into the furnace chamber, the substrate material is biased at -100--200 V, and the polishing time is 5-30 min, until the surface roughness of the VN coating reaches Ra=5-15 nm.
[0072] Wherein, in terms of atomic percentage, in the cathode arc TiAl target, the content of Ti is 10-30%, and the content of Al is 70-90%.
[0073] In the present invention, the advantages of using the above ratio of Ti and Al in the cathode arc TiAl target are: during the deposition process, TiAlN is not easy to form lattice defects, reducing the generation of tensile stress and affecting the coating performance.
[0074] In the VN layer of the VN coating and the nano-TiAlN / VN alternating coating of the present invention, the atomic percentage of V is 45 to 69 at.%, and the atomic percentage of N is 31 to 55 at.%;
[0075] In the TiAlN coating and the TiAlN layer in the nano-TiAlN / VN alternating coating, the atomic percentage of each element is as follows:
[0076] Ti: 11% to 29%, Al: 22% to 33%, N: 41% to 73%.
[0077] In the present invention, the advantage of using the above atomic percentages of V and N in the VN coating is that during the deposition process, V + The ions can better combine with the metal surface to form a pure metal transition layer. The advantage of using the above atomic percentages of Ti, Al and N in the TiAlN coating is that during the deposition process, TiAlN is not easy to form lattice defects, reducing the generation of tensile stress and affecting the coating performance.
[0078] The following is a detailed description of a method for preparing a composite coating for a titanium alloy cutting tool of the present application in combination with embodiments and experimental data.
[0079] Example 1
[0080] This embodiment provides a method for preparing a composite coating of a titanium alloy cutting tool, which specifically includes:
[0081] 1) The surface of the cemented carbide substrate was ground and polished, then ultrasonically cleaned in ethanol, dried, and placed in the furnace chamber of a coating furnace (Huasheng HT3000) and evacuated to a vacuum degree of 3×10 -3 Pa.
[0082] 2) The cemented carbide substrate material was heated to 400°C, the substrate material bias voltage was set to -150V, and 300sccm of argon gas was introduced into the furnace chamber to Ar the surface of the substrate material. + Etching, etching time 20min; then the substrate material is set to bias -1000V, three TiAl targets are turned on, the distance between the TiAl target and the substrate material is 5cm, the target current is 200A, and high energy Ti + and Al + The base material is etched for 5 minutes.
[0083] 3) The bias voltage of the substrate material was turned off and then reopened with the bias gradient increased to 0, -20 V, -40 V and -80 V respectively. Argon and nitrogen were introduced at the same time. The gas flow ratio of N2 to Ar2 was 5:7, the total flow rate of the mixed gas was 300 sccm, the working targets were 3 cathode arc TiAl targets, the target current was 130 A, the frequency was 45 kHz, the duty cycle was 43%, and the deposition time was 30 min to achieve the deposition of TiAlN coating on the surface of the substrate material.
[0084] 4) Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total flow rate of the mixed gas is 300 sccm, the rotation speed of the substrate material is 4 rpm, the working targets are three cathode arc TiAl targets and one magnetron sputtering V target, the TiAl target current is 160 A, the V target current is 10 A, the frequency is 45 KHz, the duty cycle is 43%, the substrate material bias is -80 V, the deposition time is 20 min, and the deposition of nano TiAlN / VN alternating coating on the surface of the TiAlN coating is achieved, and the modulation ratio is 1:4.
[0085] 5) Continue to introduce argon and nitrogen into the furnace chamber, with a gas flow ratio of N2 to Ar2 of 5:7, a total flow rate of the mixed gas of 300 sccm, a working target material being a magnetron sputtering V target, a target current of 10 A, a frequency of 45 kHz, a duty cycle of 43%, a matrix material bias voltage growth step of 20 V, bias voltage changes of 0 V, -20 V, -40 V and -80 V, respectively, and a deposition time of 30 min, to achieve deposition of a VN coating on the surface of the nano-TiAlN / VN alternating coating.
[0086] 6) 200 sccm of argon gas was introduced into the furnace chamber, the substrate material was biased at -120 V, and the polishing time was 25 min until the surface roughness of the VN coating reached Ra = 12 nm.
[0087] Wherein, in terms of atomic percentage, the content of Ti in the cathode arc TiAl target is 30%, and the content of Al is 70%.
[0088] The composite coating prepared in this embodiment is from the outside to the inside: 0.5μm VN coating, 5 layers of 2nm TiAlN / 7nm VN alternating coating and 1.3um TiAlN coating. There are no pores or cracks between the coating and the substrate, good toughness, high bonding strength, bonding force of 69N, coating hardness of 28±0.37GPaGPa, excellent high temperature stability, heated to more than 700℃ using a high temperature oxidation tester, its hardness remains unchanged, and no obvious oxygen content is found in the EDS analysis of the sample using a scanning electron microscope, and the friction coefficient is low. When grinding with a ZrO2 ball, the friction coefficient is 0.11.
[0089] Example 2
[0090] This embodiment provides a method for preparing a composite coating of a titanium alloy cutting tool, which specifically includes:
[0091] 1) The surface of the metal ceramic substrate material is ground and polished, then ultrasonically cleaned in ethanol, dried, placed in the furnace chamber of the coating furnace, and evacuated to a vacuum degree of 3×10 -3 Pa.
[0092] 2) The metal ceramic substrate material was heated to 400°C, the substrate material bias voltage was set to -120V, and 300sccm of argon gas was introduced into the furnace chamber to Ar the surface of the substrate material. + Etching, etching time 30min; then the substrate material was set to bias voltage -1000V, three TiAl targets were turned on, the distance between the TiAl target and the substrate material was 5cm, the target current was 150A, and high energy Ti + and Al + The base material is etched for 5 minutes.
[0093] 3) The bias voltage of the substrate material was turned off and then reopened, and the bias gradient was increased to 0, -20 V, -40 V and -80 V respectively. 300 sccm nitrogen was introduced, and the working targets were 3 cathode arc TiAl targets. The target current was 180 A, the frequency was 60 kHz, the duty cycle was 30%, and the deposition time was 30 min to achieve the deposition of TiAlN coating on the surface of the substrate material.
[0094] 4) Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total flow rate of the mixed gas is 450 sccm, the rotation speed of the substrate material is 4 rpm, the working targets are three cathode arc TiAl targets and one magnetron sputtering V target, the TiAl target current is 120 A, the V target current is 8 A, the frequency is 45 kHz, the duty cycle is 43%, the substrate material bias is -80 V, the deposition time is 20 min, and the deposition of nano TiAlN / VN alternating coating on the surface of the TiAlN coating is achieved, and the modulation ratio is 1:4.
[0095] 5) Continue to introduce argon and nitrogen into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total flow rate of the mixed gas is 450sccm, the working target is a magnetron sputtering V target, the target current is 8A, the frequency is 45KHz, the duty cycle is 43%, the matrix material bias growth step is 20V, the bias changes are 0V, -20V, -40V and -80V respectively, and the deposition time is 25min, to achieve the deposition of VN coating on the surface of the nano TiAlN / VN alternating coating.
[0096] 6) 230 sccm of argon gas was introduced into the furnace chamber, the substrate material was biased at -150 V, and the polishing time was 12 min, until the surface roughness of the VN coating reached Ra = 8 nm.
[0097] The composite coating prepared in this example is from the outside to the inside: 0.7μm VN coating, 10 layers of 3nm TiAlN / 9nm VN alternating coating and 1.1um TiAlN coating. There is no pore or crack between the coating and the substrate, good toughness, high bonding strength, bonding force of 71N, coating hardness of 29±0.45GPaGPa, excellent high temperature stability, low friction coefficient, and when grinding with ZrO2 ball, the friction coefficient is 0.15.
[0098] Example 3
[0099] This embodiment provides a method for preparing a composite coating of a titanium alloy cutting tool, which specifically includes:
[0100] 1) The surface of the stainless steel substrate was ground and polished, then ultrasonically cleaned in ethanol, dried, and placed in the furnace chamber of the coating furnace, and vacuumed to a vacuum degree of 3×10 -3 Pa.
[0101] 2) The stainless steel substrate material was heated to 400°C, the substrate material bias voltage was set to -150V, and 300sccm of argon gas was introduced into the furnace chamber to Ar the surface of the substrate material. + Etching, etching time 30min; then the substrate material was set to bias -800V, three TiAl targets were turned on, the distance between the TiAl target and the substrate material was 5cm, the target current was 180A, and high energy Ti + and Al + The base material is etched for 5 minutes.
[0102] 3) The bias voltage of the substrate material was turned off and then reopened with the bias gradient increased to 0, -20 V, -40 V and -80 V respectively, 300 sccm nitrogen was introduced, the working targets were 3 cathode arc TiAl targets, the target current was 160 A, the frequency was 60 kHz, the duty cycle was 60%, and the deposition time was 20 min to achieve the deposition of TiAlN coating on the surface of the substrate material.
[0103] 4) introducing argon and nitrogen into the furnace chamber, with a gas flow ratio of N2 to Ar2 of 5:7, a total flow rate of the mixed gas of 500 sccm, a substrate rotation speed of 4 rpm, three cathode arc TiAl targets and one magnetron sputtering V target as working targets, a TiAl target current of 100 A, a V target current of 12 A, a frequency of 45 kHz, a duty cycle of 43%, a substrate material bias of -80 V, a deposition time of 10 min, and achieving deposition of nano-TiAlN / VN alternating coating on the surface of the TiAlN coating, with a modulation ratio of 1:4.
[0104] 5) Continue to introduce argon and nitrogen into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total flow rate of the mixed gas is 320sccm, the working target is a magnetron sputtering V target, the target current is 12A, the frequency is 45KHz, the duty cycle is 43%, the matrix material bias growth step is 20V, the bias changes are 0V, -20V, -40V and -80V respectively, and the deposition time is 25min, to achieve the deposition of VN coating on the surface of the nano TiAlN / VN alternating coating.
[0105] 6) 300 sccm of argon gas was introduced into the furnace chamber, the substrate material was biased at -120 V, and the polishing time was 20 min until the surface roughness of the VN coating reached Ra = 6 nm.
[0106] The composite coating prepared in this example is from the outside to the inside: 0.45μm VN coating, 10 layers of 2.6nm TiAlN / 7.8nm VN alternating coatings and 1.4um TiAlN coating. There are no pores or cracks between the coating and the substrate, good toughness, high bonding strength, bonding force of 69N, coating hardness of 30±0.21GPaGPa, excellent high temperature stability, low friction coefficient, and when grinding with ZrO2 ball, the friction coefficient is 0.18.
[0107] Figure 1 This is a cross-sectional electron scanning micrograph of the TiAlN-nano TiAlN / VN-VN composite coating prepared in Example 1 of the present invention. The figure shows a typical columnar structure of a TiAlN-nano TiAlN / VN-VN composite coating deposited on a cemented carbide substrate. In the nano TiAlN / VN alternating coating, the thickness of the TiAlN layer is about 2.1 nm, and the thickness of the VN layer is about 8.2 nm.
[0108] Figure 2 The scratch morphology of the TiAlN-nano TiAlN / VN-VN composite coating designed and prepared by the present invention. The figure shows that the crack is parallel to the scratch. When the coating begins to peel off, its load L2=69.1N. As the loading load increases, the coating peels off more. When the load increases to 120N, the coating peels off in large quantities.
[0109] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0110] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0111] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a composite coating of a titanium alloy cutting tool, characterized in that: The preparation method comprises: S1. Place the clean surface substrate material into the furnace chamber of the vacuum plasma plating equipment and evacuate the chamber; S2. Use Ar + 、Ti + and Al + Etching the base material; S3. Depositing a TiAlN coating on the surface of the substrate material using a gradient bias process; S4. Depositing a nano-TiAlN / VN alternating coating on the surface of the TiAlN coating; S5. A VN coating is deposited on the surface of the nano-TiAlN / VN alternating coating by a gradient bias process; S6. Using Ar + The surface of the VN coating is polished.
2. The method for preparing a composite coating of a titanium alloy cutting tool according to claim 1, characterized in that: The step of placing the substrate material with a clean surface into a furnace chamber of a vacuum plasma plating device and evacuating the chamber specifically includes: The surface of the substrate material was ground and polished, then ultrasonically cleaned in ethanol, dried, and placed in the furnace of a vacuum plasma plating device to evacuate the surface to a vacuum degree of 3 to 6 × 10 -3 Pa.
3. The method for preparing a composite coating of a titanium alloy cutting tool according to claim 1, characterized in that: The use of Ar + 、Ti + and Al + Etching the base material includes: The substrate material is heated to 400°C, the substrate material bias voltage is set to -120 to -150V, and 150 to 350 sccm of argon is introduced into the furnace chamber to Ar + Etching, etching time 10 to 30 minutes; The base material is set to a bias voltage of -800 to -1000 V, the cathode arc TiAl target is turned on, the distance between the TiAl target and the base material is 5 cm, the target current is 60 to 200 A, the rated power is 20 kW, and the duty cycle is 45% to perform high-energy ion Ti on the base material. + and Al + Etching, etching time 5 to 15 minutes.
4. The method for preparing a composite coating of a titanium alloy cutting tool according to claim 1, characterized in that: The method of depositing a TiAlN coating on the surface of a substrate material by using a gradient bias process specifically includes: Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total flow of the two gases is 300-500sccm, the working targets are 3 cathode arc TiAl targets, the target current is 60-200A, the frequency is 30-70KHz, the duty cycle is 30%-80%, the bias gradient of the substrate material increases in steps of 20V, the bias changes are 0V, -20V, -40V and -80V respectively, and the deposition time is 20-40min to achieve the deposition of TiAlN coating on the surface of the substrate material.
5. The method for preparing a composite coating of a titanium alloy cutting tool according to claim 1, characterized in that: The step of depositing a nano-TiAlN / VN alternating coating on the surface of the TiAlN coating specifically includes: Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total gas flow is 300-500sccm, the rotation speed of the substrate material is 2-6rpm, the working targets are three cathode arc TiAl targets and one magnetron sputtering V target, the target current is 5-200A, the frequency is 30-70KHz, the duty cycle is 30%-80%, the substrate material bias voltage is -80V, the deposition time is 10-20min, and the deposition of nano TiAlN / VN alternating coating on the surface of the TiAlN coating is achieved, and the modulation ratio is 1:
4.
6. The method for preparing a composite coating of a titanium alloy cutting tool according to claim 1, characterized in that: The step of depositing a VN coating on the surface of the nano-TiAlN / VN alternating coating by using a gradient bias process specifically includes: Argon and nitrogen are introduced into the furnace chamber, the gas flow ratio of N2 to Ar2 is 5:7, the total gas flow rate is 300-500sccm, the working target material is a magnetron sputtering V target, the target current is 5-20A, the frequency is 30-70KHz, the duty cycle is 30%-80%, the matrix material bias growth step is 20V, the bias changes are 0V, -20V, -40V and -80V respectively, and the deposition time is 10-30min, so as to realize the deposition of VN coating on the surface of the nano TiAlN / VN alternating coating.
7. The method for preparing a composite coating of a titanium alloy cutting tool according to claim 1, characterized in that: The use of Ar + Polishing the surface of the VN coating specifically includes: 150-350 sccm of argon gas is introduced into the furnace chamber, the substrate material is biased at -100--200 V, and the polishing time is 5-30 min, until the surface roughness of the VN coating reaches Ra=5-15 nm.
8. A method for preparing a composite coating of a titanium alloy cutting tool according to any one of claims 3 to 5, characterized in that: In terms of atomic percentage, in the cathode arc TiAl target, the content of Ti is 10-30%, and the content of Al is 70-90%.
9. The method for preparing a composite coating of a titanium alloy cutting tool according to claim 1, characterized in that: The matrix material includes any one of cemented carbide, metal ceramic, stainless steel, single crystal silicon wafer, ceramic silicon plate and titanium alloy.
10. A titanium alloy cutting tool, characterized in that: The tool is prepared by the composite coating preparation method for a titanium alloy cutting tool according to any one of claims 1 to 9.
11. A titanium alloy cutting tool according to claim 10, characterized in that: The tool comprises a tool base material, a TiAlN coating, a nano TiAlN / VN alternating coating and a VN coating are sequentially deposited on the surface of the tool base material, the TiAlN coating has a thickness of 0.8 to 1.5 μm, the total thickness of the nano TiAlN / VN alternating coating is 0.1 to 0.5 μm, the modulation ratio is 1:4, and the VN coating has a thickness of 0.5 to 1 μm; In the VN coating and the VN layer in the nano-TiAlN / VN alternating coating, the atomic percentage of V is 45 to 69 at.%, and the atomic percentage of N is 31 to 55 at.%; In the TiAlN coating and the TiAlN layer in the nano-TiAlN / VN alternating coating, the atomic percentage of each element is as follows: Ti: 11% to 29%, Al: 22% to 33%, N: 41% to 73%.
12. Use of a titanium alloy cutting tool as claimed in claim 10 or 11 in cutting materials with high strength and low thermal conductivity, characterized in that: The material with high strength and low thermal conductivity includes any one of titanium alloy, ultra-high strength steel and high temperature alloy.
